Growing Groups, Cooperation, and the Rate of Entry - Eva Ranehill; Frédéric Schneider; Roberto A. Weber (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the stability of voluntary cooperation in response to varying rates at which a group grows. Using a laboratory public-good game with voluntary contributions and economies of scale, we construct a situation in which expanding a group's size yields potential efficiency gains, but only if the group overcomes the challenge that growth poses for sustained cooperation. We then study the effect on cooperation of exogenously varying rates of entry. Slow growth yields higher cooperation rates and welfare than fast growth, both for incumbents and entrants. This is consistent with slow growth allowing the persistence of optimistic self-reinforcing beliefs. We also study growth rates determined by incumbent group members. While such endogenous growth generally also produces high cooperation levels, growth stalls at intermediate group sizes, leaving potential efficiency gains from growth unrealized.
Keywords: C92; C72; 330; voluntary cooperation; experiment; public good game; endogenous growth